2020
DOI: 10.1111/ajt.15826
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study to define the epidemiology and outcomes of Clostridioides difficile infection in pediatric hematopoietic cell and solid organ transplant recipients

Abstract: Hematopoietic cell transplant (HCT) and solid organ transplant (SOT) recipients are at increased risk for Clostridioides difficile infection (CDI). We conducted a multicenter retrospective study to describe the incidence of CDI in children transplanted between January 2010 and June 2013. Nested case-control substudies, matched 1:1 by transplant type, institution, patient age, and time of year (quartile) of transplant, identified CDI risk factors. Cohorts included 1496 HCT and 1090 SOT recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…In pediatric SOT recipients, infectious causes of diarrhea remain poorly defined. The incidence of Clostridioides difficile among pediatric SOT recipients with diarrhea has been reported to be 7.3‐24% 19,20 . In other pediatric series, vaccine‐preventable rotavirus infections were the most frequent pathogen identified in 3‐11%, with highest prevalence in liver and intestinal transplant recipients 21‐23 .…”
Section: Etiologymentioning
confidence: 96%
“…In pediatric SOT recipients, infectious causes of diarrhea remain poorly defined. The incidence of Clostridioides difficile among pediatric SOT recipients with diarrhea has been reported to be 7.3‐24% 19,20 . In other pediatric series, vaccine‐preventable rotavirus infections were the most frequent pathogen identified in 3‐11%, with highest prevalence in liver and intestinal transplant recipients 21‐23 .…”
Section: Etiologymentioning
confidence: 96%
“…An altered microbiota was also found in individuals with autoimmune disorders, allergies, cancer, diabetes, and inflammatory bowel disease [23]. Other specific populations at an increased risk of CDI include hematopoietic cell transplants (HCT), oncology patients and solid organ transplant recipients [24][25][26][27]; the presence of a gastrostomy or jejunostomy tube has also been found to be an additional independent risk factor for CDI in children [28]. Interestingly, paediatric CDI has been reported as a complication in paediatric appendicitis [29].…”
Section: Laboratory Diagnostics For Clostridioides Difficile Infectio...mentioning
confidence: 99%
“…The studies were conducted in China, the United States, Japan, Spain, Italy, New Zealand, and other European countries. Seventeen studies [18,19,22,24,25,27,28,30,32,33,35,[37][38][39][40][41][42] were of high quality and eight studies [20,21,23,26,29,31,34,36] were of moderate quality. Assessment of methodological quality is presented in Supplementary Tables SⅡ-SⅢ.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Four studies reported data on gender as a risk factor for CDI [20,28,31,35]. Metaanalysis of the four included studies showed a significantly increased risk of CDI associated with male gender (OR, 1.18; 95% CI, 1.05-1.32; P=0.005).…”
Section: Gendermentioning
confidence: 99%